2009
DOI: 10.1111/j.1365-2958.2009.06832.x
|View full text |Cite
|
Sign up to set email alerts
|

Global position analysis of the Pseudomonas aeruginosa quorum‐sensing transcription factor LasR

Abstract: SummaryIn Pseudomonas aeruginosa quorum sensing (QS), the transcriptional regulator LasR controls the expression of more than 300 genes. Several of these genes are activated indirectly via a second, subordinate QS regulator, RhlR. Conserved sequence elements upstream of individual other genes have been shown to bind LasR in vitro. To comprehensively identify all regions that are bound by LasR in vivo, we employed chromatin immunoprecipitation in conjunction with microarray analysis. We identified 35 putative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
221
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(228 citation statements)
references
References 70 publications
(150 reference statements)
5
221
0
2
Order By: Relevance
“…LasR, the most upstream QS regulon in the P. aeruginosa QS hierarchy, regulates the expression of more than 300 virulenceassociated genes (17). However, recent genetic studies using diverse P. aeruginosa clinical isolates reported that adaptive mutations in the lasR gene occur spontaneously in the course of chronic airway infection in CF (9,12,19,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LasR, the most upstream QS regulon in the P. aeruginosa QS hierarchy, regulates the expression of more than 300 virulenceassociated genes (17). However, recent genetic studies using diverse P. aeruginosa clinical isolates reported that adaptive mutations in the lasR gene occur spontaneously in the course of chronic airway infection in CF (9,12,19,42).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we sought to elucidate the effect of suppressed synthesis of PAI-1 and PAI-2 on the expression of downstream virulence genes. We tested eight genes reported to be directly regulated by LasR (17). Figure 5A shows the relative expression of these selected genes as measured by quantitative RT-PCR analysis.…”
Section: Vol 79 2011 Suppressed Qs In P Aeruginosa During Anaerobimentioning
confidence: 99%
“…When LasR/3O-C12-HSL binding to DNA was studied in vivo by immunoprecipitation of chromatin, a third las box was described (Gilbert et al, 2009). This las box (rhlR-3 las box, Fig.…”
Section: Lasr-binding Sequences Overlap Vbs1 and Vbs2mentioning
confidence: 99%
“…LasR/3-O-C12-HSL transcriptional regulation of rhlR was shown to be due to its activation of promoter 1 through its binding to a las box (the rhlR-1 las box), and possibly also of promoter 4 (Medina et al, 2003a). A second LasR/3O-C12-HSL-binding site was identified upstream of rhlR promoter 1 by the analysis of DNA sequences after immunoprecipitation of DNA-LasR complexes (Gilbert et al, 2009). Transcription initiation at promoter 2 was shown to be constitutive.…”
Section: Introductionmentioning
confidence: 99%
“…Its transcription appears to be activated by LasR (Gilbert et al, 2009), and it is thought to function analogously to the QS antiactivator TraM in Agrobacterium tumefaciens (Fuqua et al, 1995;Piper and Farrand, 2000). QteE represses the expression of several las and rhl-dependent target genes by independently reducing LasR and RhlR protein stability, probably through direct protein-protein interaction (Siehnel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%